Beyond common sense : psychological science in the courtroom - Borgida, Eugene; Fiske, Susan T.; Wiley InterScience (Online service) (Malden, MA : Blackwell Pub., 2008)
Abstract
Race, crime, and antidiscrimination / R. Richard Banks, Jennifer L. Eberhardt, and Lee Ross -- Discrimination in America and legal strategies for reducing it / Faye J. Crosby and John F. Dovidio -- The young science of prejudice against older adults : established answers and open questions about ageism / Todd D. Nelson -- Gender prejudice : on the risks of occupying incongruent roles / Alice H. Eagly and Anne M. Koenig -- From the laboratory to the bench : gender stereotyping research in the courtroom / Laurie A. Rudman, Peter Glick, and Julie E. Phelan -- (Un)common knowledge : the legal viability of sexual harassment research / Louise F. Fitzgerald and Linda L. Collinsworth -- Subjectivity in the appraisal process : a facilitator of gender bias in work settings / Madeline E. Heilman and Michelle C. Haynes -- Eyewitness identification : issues in common knowledge and generalization / Gary L. Wells and Lisa E. Hasel -- Repressed and recovered memory / Elizabeth F. Loftus, Maryanne Garry, and Harlene Hayne -- Expert testimony on the psychology of confessions : a pyramidal framework of the relevant science / Saul M. Kassin -- Polygraph testing / William G. Iacono -- Social science and the evolving standards of death penalty law / Phoebe C. Ellsworth and Samuel R. Gross -- Pretrial publicity : effects, remedies, and judicial knowledge / Margaret Bull Kovera and Sarah M. Greathouse -- Media violence, aggression, and public policy / Craig A. Anderson and Douglas A. Gentile -- The limits of science in the courtroom / David L. Faigman -- Research on eyewitness testimony and false confessions / Margaret A. Berger -- Commentary on research relevant to sex discrimination and sexual harassment / Barbara A. Gutek -- The tenuous bridge between research and reality : the importance of research design in inferences regarding work behavior / Frank J. Landy -- Psychological contributions to evaluating witness testimony / Shari Seidman Diamond -- Beyond common-sense understandings of sex and race discrimination / R. Richard Banks -- Behavioral realism in law : reframing the discussion about social science's place in antidiscrimination law and policy / Linda Hamilton Krieger.
Includes bibliographical references and index.
Print version record.
Keywords: Forensic psychology -- United States; Justice, Administration of -- United States -- Psychological aspects; Discrimination in justice administration -- United States -- Psychological aspects; Discrimination -- United States; Physical-appearance-based bias; Electronic books